Modeling financial market volatility in transition markets: A multivariate case - Leoni Eleni Oikonomikou (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
This paper presents evidence of linkages across equity markets in the following transition economies: Russia, Ukraine, Poland and Czech Republic from beginning of January 2005 till the end of December 2014. We apply a multivariate asymmetric EGARCH model. Empirical results indicate significant return and volatility spillover effects during the full sample and the Russian Great Recession and Ukrainian crisis episodes. Over the full sample period, there is evidence of return co-movements, and strong volatility persistence. During the Russian Great Recession subsample, the ownreturn effects of the markets are stronger than the cross-market effects and their correlations have increased. Finally, the Ukrainian political crisis indicated no clear information producer, whereas, evidence of returns co-movement still exists. The markets in question are mainly partially integrated and the volatility transmission linkages across them are not that strong in crises periods, thus confirming previous literature on the particularities of emerging and frontier markets. According to the empirical finance literature, developed markets are interconnected. However, emerging markets are mainly affected by local shocks. The same applies to frontier markets. Based on the categorization of countries based on their financial market development: frontier markets are in embryonic stages of financial development (in this case, Ukraine), emerging markets are important financial markets, not fully modernized belonging to countries well developed to attract capital (in this case, Russia, Poland and Czech Republic), and developed markets.
Keywords: G01; G15; 330; multivariate EGARCH models; spillover effects; transition markets; equity markets